Buddhist Teachings, Spirituality and Female Entrepreneurs’ Business Decisions in Sri Lanka - Perera, L.E.A.N.; Surangi, H.A.K.N.S. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2021)
Purpose – Female entrepreneurship has been pointed out by researchers as well as policymakers as one of the main drivers of economic and social development in any country. Over the years, a great deal of research has been conducted on the area of female entrepreneurship. However, to date, there has not been much discussion of the area of female entrepreneurs’ religious behaviour which is remarkable. Hence, this study examines the nature of female entrepreneurs’ religious behavior and how Buddhist teachings and Buddhist spirituality influence business decisions of female entrepreneurs, during start- ups throughout the ongoing business operations. Although Buddhism is a vast literature, this study focuses mainly on the five precepts. Design/methodology/approach – This study is based on social constructionism philosophy and narrative design was used to explore the female entrepreneurs’ religious behavior. A snowball sampling procedure was applied, and seven interviews were conducted to generate data for the study. This qualitative data analysis was complemented and supported with data from narrative in-depth interviews, observations and collected documents and field notes. Findings – Findings revealed that Buddhist female entrepreneurs’ business decisions are influenced by their religious teachings, especially the five precepts and religious spirituality. Those decisions are related to the start-up, operations, pricing, networks, profit sharing, finance, problem solving and sustainability. According to the results, female entrepreneurs have engaged in strong religious practice in their businesses and their personal lives since their childhood. Buddhist teachings and spirituality can be identified as the key factor of business success and work-life satisfaction of Buddhist female entrepreneurs in Sri Lanka. Implications – The findings can support the facilitating and promoting of spiritual entrepreneurship among entrepreneurs. It could be of valuable use to furthering our understanding of the role of Buddhist teachings and spirituality on entrepreneurs’ business decisions and the influence of other religious teachings and spiritualties in fostering decision making among entrepreneurs.
Keywords: Buddhist teachings, Five Precepts, Buddhist spirituality, Female entrepreneurs, Business decisions, Qualitative